2015
DOI: 10.1038/ncomms8116
|View full text |Cite
|
Sign up to set email alerts
|

Planctomycetes do possess a peptidoglycan cell wall

Abstract: Most bacteria contain a peptidoglycan (PG) cell wall, which is critical for maintenance of shape and important for cell division. In contrast, Planctomycetes have been proposed to produce a proteinaceous cell wall devoid of PG. The apparent absence of PG has been used as an argument for the putative planctomycetal ancestry of all bacterial lineages. Here we show, employing multiple bioinformatic methods, that planctomycetal genomes encode proteins required for PG synthesis. Furthermore, we biochemically demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 51 publications
6
127
1
3
Order By: Relevance
“…Most recently, the detection of peptidoglycan in the cell wall of planctomycetes, including G. obscuriglobus (16,17), supports the interpretation of the G. obscuriglobus cell plan as Gram negative. The absence of peptidoglycan and presence of a proteinaceous cell wall (18) had long been distinguishing planctomycete features that led to the proposal of a unique cell plan for all planctomycetes (3,5,6,13,19).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Most recently, the detection of peptidoglycan in the cell wall of planctomycetes, including G. obscuriglobus (16,17), supports the interpretation of the G. obscuriglobus cell plan as Gram negative. The absence of peptidoglycan and presence of a proteinaceous cell wall (18) had long been distinguishing planctomycete features that led to the proposal of a unique cell plan for all planctomycetes (3,5,6,13,19).…”
mentioning
confidence: 88%
“…The pursuit of this question, together with studies of the structural connections between the LPS of G. obscuriglobus (and possibly other planctomycetes) and the newly discovered planctomycete peptidoglycans (16,17), will shed more light on what is now emerging as the planctomycete variation on the Gram-negative cell plan (20). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their impact on outcome after surgical treatment of CTS is not known. A recent case-control study [7] suggested that metabolic syndrome is related to more severe forms of CTS, as well as to longer recovery time after OCTR, but not to worse improvement after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Suddenly, one imagines the natural evolution of walled FtsZ-less bacteria as perhaps a rather pedestrian affair. In fact, it is not so hard to imagine coli-flowering as a clumsy prelude to the budding-mode of propagation common amongst the walled FtsZ-less Planctomycetes 14, 15 . Allowing CFL mutants to further evolve under various conditions might be enlightening as well as entertaining.…”
mentioning
confidence: 99%